FACTORS IN CULTURAL ENVIRONMENT BUILDING IN INDRA IN THE 1920-30s - Lendiņa, Mirdza (Via Latgalica, 2008)
The region of Latgale, which borders the big, expansive neighbour Russia, Poland, Belorussia and Lithuania, has survived the most difficult years of subjection to foreign states. An almost 300-year-long administrative isolation from the other regions of Latvian culture has caused a specific development of language and social traditions in a multinational area. In 2007, the project „Field studies in the rural municipality of Indra in the region of Kraslava – traditions, language, cultural environment” was developed at Rēzekne University College for the research of this topic. It was based on ethnolinguistic data obtained through interviews with the population of Indra municipality. This article addresses the following questions: 1) What are the historic origins of this population, and when and from where did these people come to this rural municipality to settle permanently? 2) How did the newcomers influence the formation of a cultural environment in Indra and why was that important? The objective of the paper is to reveal the specifics and the typical features of the cultural environment of Indra in the context of Latgale. According to historical data and the memories of Benita Drozdova, the Latvian language was already in the 1930s the link that brought together different nationalities for common public work in Indra municipality. State policies in the field of education, local training of Latgalian specialists in Rezekne and Daugavpils, and the migration of specialists from other regions with no official language problems were some of the reasons which contributed to a better education of society and an increase in prosperity, which made Latgale move closer to the other regions of Latvia. This is illuminated by the visual materials attached to the analysis, which show that the border station of Indra was a vibrant cultural environment in the end of the 30’s where a local intelligentsia representing different professions had been formed.